PENGARUH PERTUMBUHAN EKONOMI TERHADAP TINGKAT KEMISKINAN KABUPATEN/KOTA DI KALIMANTAN BARAT TAHUN 2007-2011 - B01108011, Marselia (Jurnal Curvanomic, 2013)
The Research aimstoanalyze The Influence of Regency/Municipality Economic GrowthTowardRegency/Municipality Povertyin Kalimantan Barat. In this Research,the writesemploys descriptivemethodtoobserveindependent variabel (Economic growth) toward dependen variabel (poverty) which thenanalyzed byusing eviews 6 with panel regression model and statistic allyanalysis toolsnamely t test and determination coeficientin order toreach a conclusionthat Economic growth possessin fluencetoward poverty. The increasing economic growth but can not cope with the speed of growth is due to the poverty level of income inequality in a region and the growth occurred in the sectors that are not essential to alleviating poverty rate that occurred in the province of West Kalimantan. Keyword: effect of economic growth on poverty districts / cities in West Kalimantan province.